EVALUATION OF PHYSIOLOGY LABORATORY TEACHING BY STUDENTS’ FEEDBACK - Sandhu, Parminder Kaur; ., Dimple; Dhillon, Sukhjinder Kaur; Sandhu, Ravneet; Kaur, Harkirat (Pakistan Journal of Physiology, 2015)
The evaluation of the learning experience and the effective use of student feedback can benefit all those with a stake in high quality teaching and learning: students, teaching staff, department and college. Feedback in medical teaching is an important part of medical education. This study was conducted with an aim to improve teaching in physiology practicals by taking student feedback at Department of Physiology, Sri Guru Ram Das Institute of Medical Sciences and Research, Sri Amritsar. Methods: All the second semester medical students of batch 2014 (males: 73 and females: 137) were given a pre-validated questionnaire which enclosed 10 questions (to be responded on a 5 point Likert scale) with reference to syllabus and teaching. It also had 3 open ended questions about strengths and weaknesses of laboratory teaching. Descriptive statistics were used and results were expressed as percentage. Results: 120 females and 63 males returned the filled questionnaire. Majority of students found teaching and learning in the physiology laboratory motivating and of assistance for next semesters. They were happy as performing practicals helped in clearing concepts, developing clinical skills, better understanding of theoretical topics, broadening the range of thinking. They were unhappy about outdated apparatus, long demonstrations, less number of equipments, writing of practical files, not performing animal experiments and less number of practicals. The results were presented at Departmental meeting and remedial measures were initiated.